HUMANITARIAN MILITARY INTERVENTION IN KOSOVO AND LIBYA: AN ASSESSMENT ON RELEVANT THEORIES OF INTERNATIONAL RELATIONS - Datta, Sujit (European Scientific Journal, ESJ, 2014)
The paper aims to makes an elaborate discussion on military and humanitarian interventions under relevant theories of international relations. An examination of NATO intervention in Kosovo and Libya revels that, states responses to humanitarian crises have not dramatically changed before and after R2P was adopted. Although the adoption of R2P represents significant progress of the liberal school, the realist critique of R2P should be seriously considered to avoid intervention based on national interests of great powers. Considering the fact that the intervention in Libya was undertaken to preserve national interests of some of NATO member states, the selectivity of intervention is likely to occur in the future, meaning that states would not intervene in humanitarian crises if their national interests are not at stake.